Ladies of the Ticker : Women and Wall Street from the Gilded Age to the Great Depression - Robb, George (Book collections on Project MUSE., 2017)
"Long overlooked in histories of finance, women played an essential role in areas such as banking and the stock market during the late nineteenth and early twentieth centuries. Yet their presence sparked ongoing controversy. Hetty Green's golden touch brought her millions, but she outraged critics with her rejection of domesticity. Progressives like Victoria Woodhull, meanwhile, saw financial acumen as more important for women than the vote. George Robb's pioneering study sheds a light on the financial methods, accomplishments, and careers of three generations of women. Plumbing sources from stock brokers' ledgers to media coverage, Robb reveals the many ways women invested their capital while exploring their differing sources of information, approaches to finance, interactions with markets, and levels of expertise. He also rediscovers the forgotten women bankers, brokers, and speculators who blazed new trails--and sparked public outcries over women's unsuitability for the predatory rough-and-tumble of market capitalism. Entertaining and vivid with details, Ladies of the Ticker sheds light on the trailblazers who transformed Wall Street into a place for women's work."--